Men in Aïda - Melnick, David J. (punctum books, 2014)
David J. Melnick published the first book of Men in Aida, a homophonic, but also homoeroticized translation of Homer's epic Iliad, in December 1983 in an edition of 450 at Tuumba Press. After appearing in many guises and fragments, Book Two was published online in 2002 as part of the Eclipse Archive. Book Three appears for the first time in the present publication, which brings together all three books of one of the most important American avant-garde poems.